Prognostic value of pre-operative peripheral inflammation markers in patients with squamous cell carcinoma of the external auditory canal - Li,Feitian (2022)
Abstract Introduction: Squamous cell carcinoma of the external auditory canal is a rare entity. Previous studies have suggested predictors for tumor recurrence. However, most of the prognostic factors were from the clinicopathological aspect. Objective: This study aims to analyze the correlation between pre-operative peripheral inflammation markers and survival outcomes, in order to identify prognostic biomarkers for patients with squamous cell carcinoma of the external auditory canal. Methods: We retrospectively analyzed patients diagnosed with squamous cell carcinoma of the external auditory canal who underwent surgery at our institute. The pre-operative circulating inflammatory markers, such as the neutrophil, lymphocyte, platelet, and monocyte counts were measured and their ratios including neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and lymphocyte-to-monocyte ratio were calculated. The prognostic value of the measured hematologic parameters in relation to the survival outcomes was also evaluated. Results: A total of 83 patients were included, of which 26 patients showed tumor recurrence and 57 without recurrence. Neutrophil counts and neutrophil-to-lymphocyte ratio were closely connected with tumor stage. In the patients with recurrence, neutrophil counts, neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were elevated (p< 0.0001, p< 0.0001 and p = 0.001), while lymphocyte counts and lymphocyte-to-monocyte ratio were decreased (p = 0.013 and p = 0.016, respectively). The receiver operating curve analysis indicated that pre-operative neutrophil-to-lymphocyte ratio is a potential prognostic marker for recurrence of squamous cell carcinoma of the external auditory canal (area under curve = 0.816), and the cut-off points was 2.325. Conclusions: Pre-operative neutrophil and lymphocyte counts, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte are significantly correlated with tumor recurrence in patients with external auditory canal squamous cell carcinoma. Furthermore, neutrophil-to-lymphocyte ratio may be unfavorable prognostic factors of this disease.